2019
DOI: 10.21203/rs.2.14759/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Young-Onset Colorectal Cancer in the North East of Scotland: Survival, Clinico-Pathological Features and Genetics

Abstract: Background Colorectal cancer (CRC) in patients aged under 55 years is on the rise, constituting approximately 10% of cases. Our aim was to determine the survival and clinico-pathological details of young-onset CRC (yCRC), as well as audit the referral rate to genetic services and thus establish the incidence of microsatellite instability (MSI). Methods A retrospective case note review was conducted for patients aged under 55 years who were diagnosed with CRC between 2005-2015 in the North East of Scotland. Cas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Furthermore, we found that more than 39% of our cases were first diagnosed with CRC when still under 50 years. We also found that the mean age for early-onset CRCs was 40 years and that the highest number of cases were in the final decade of the age range investigated (40-50 years of age), which is in accordance with other studies [9,11,16,48]. However, this pattern is more pronounced in Asia than in the Western countries [38,[49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, we found that more than 39% of our cases were first diagnosed with CRC when still under 50 years. We also found that the mean age for early-onset CRCs was 40 years and that the highest number of cases were in the final decade of the age range investigated (40-50 years of age), which is in accordance with other studies [9,11,16,48]. However, this pattern is more pronounced in Asia than in the Western countries [38,[49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
“…In the last 10 years, a large number of research projects around the world have focused on early-onset CRC. The sample size of these studies ranged between 49 and 64,068 cases [5, 7-18, 48, 56-58] and the mean age of study subjects ranged between 37 and 47 years [5,[7][8][9][10][11][12][14][15][16][17][18]. In contrast to our study, the frequency of earlyonset CRC is generally reported to be higher in men than in women [5,7,10,11,[13][14][15][16][17]48], but various studies have yielded conflicting results [10,28,47,59].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, the relationship is not particularly specific; with around 67 million courses of antibiotics prescribed each year in the USA to children aged less than 19 [18], exposure to antibiotics among the young is incredibly common. It is therefore hard to judge how many of these exposed individuals will potentially be diagnosed with earlyonset CRC-a relatively rare disease outcome [9].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern may be related; antibiotic consumption has been associated with CRC genesis in adults of all ages [4][5][6][7][8]. In contrast to declining incidence amongst older populations [5,9], CRC incidence among adults aged 20-29 years in Europe is increasing by ~8% each year [1]. In the USA, CRC is the second most common incident cancer and third leading cause of cancer death in adult males less than 50 years old [10].…”
Section: Introductionmentioning
confidence: 99%